The study of possibility to elevate antitumor activity and decrease of systemic toxic effects of cisplatin by its binding with deliganded albumin - Sakhno, L.A.; Sarnatskaya, V.V.; Yushko, L.A.; Melnikov, O.R.; Momot, V.Ya.; Korneeva, L.N.; Svintsiskiy, V.S.; Korotich, V.G.; Nechitaylo, I.I.; Nikolaev, V.G. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
Aim: To evaluate antitumor and toxic action of cisplatin (CP) in non-bound form and in a complex with deliganded albumin. Methods: To study complex-formation between CP and albumin, differential scanning and isothermic flow microcalorimetry were used. For quantitive evaluation of albumin-bound CP, the method of ultrafiltration was applied. Concentration of platinum in the samples was determined by atomic-absorption spectral analysis. Antitumor and toxic effect of CP and CP-albumin complex was studied in vivo using Guerin carcinoma (GC) model. Results: It has been shown that the second drug-binding site, located in the III domain of albumin molecule is one of the main points of binding of CP. Purification of officinal human serum albumin (HSA) on highly active carbon hemosorbents of HSGD mark allows to obtain deliganded albumin (dHSA) with elevated complex-forming ability toward CP. Administration of CP-dHSA complex provides higher rate of GC growth inhibition, than that of CP, and the content of creatinine in blood plasma of GC-bearing rats increases by 15% versus 40% in the case of CP administration. Conclusion: The data obtained allow recommend application of CP-dHSA to complex for enhancement of antitumor action and decrease of toxic effects of cisplatin. Цель: оценить противоопухолевое и токсическое действие цисплатина (ЦП) в свободной форме и в комплексе с делигандизированным
альбумином. Методы: дифференциальную сканирующую и изотермичную проточную микрокалориметрию использовали для
исследования комплексообразования ЦП с альбумином. Для количественной оценки связанного с альбумином цитостатика
использовали метод ультрафильтрации. Концентрацию платины в образцах определяли методом атомно-абсорбционного
спектрального анализа. Противоопухолевый и токсический эффекты ЦП и ЦП в комплексе с делигандизированным альбумином
изучали на крысах с карциномой Герена. Результаты: показано, что одним из основных мест связывания ЦП является второй
лекарственный сайт, расположенный в III домене молекулы альбумина. Очистка фармакопейного сывороточного альбумина (ЧСА) на
высокоактивных углеродных гемосорбентах марки ГСГД позволяет получить делигандизированный альбумин (дЧСА) с повышенной
комплексообразующей способностью в отношении ЦП. ЦП в связанной с дЧСА форме обеспечивает повышение ингибирующего
влияния цитостатика на рост карциномы Герена, при этом содержание креатинина в плазме крови повышается на 15% по сравнению
с 40% при использовании несвязанного ЦП. Выводы: результаты проведенных исследований дают основания рекомендовать
использование ЦП в комплексе с альбумином для усиления его противоопухолевого действия и снижения токсических эффектов.